2016
DOI: 10.1103/physreva.93.022513
|View full text |Cite
|
Sign up to set email alerts
|

Tabulation of the bound-state energies of atomic hydrogen

Abstract: We present tables for the bound-state energies for atomic hydrogen. The tabulated energies include the hyperfine structure, and thus this work extends the work of Rev. Mod. Phys. 84, 1527(2012, which excludes hyperfine structure. The tabulation includes corrections of the hyperfine structure due to the anomalous moment of the electron, due to the finite mass of the proton, and due to off-diagonal matrix elements of the hyperfine Hamiltonian. These corrections are treated incorrectly in most other works. Simple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 42 publications
8
66
2
Order By: Relevance
“…(7.1)) and ν 3/2 (Eq. (7.2)) are used to determine the fine structure splitting ∆ν [4,[43][44][45]. With a difference of -0.6 (2.8) kHz, our experimental result is in excellent agreement with the theoretical value and represents the most accurate optical determination of a fine structure splitting in atomic hydrogen.…”
Section: P Fine Structure Intervalsupporting
confidence: 75%
“…(7.1)) and ν 3/2 (Eq. (7.2)) are used to determine the fine structure splitting ∆ν [4,[43][44][45]. With a difference of -0.6 (2.8) kHz, our experimental result is in excellent agreement with the theoretical value and represents the most accurate optical determination of a fine structure splitting in atomic hydrogen.…”
Section: P Fine Structure Intervalsupporting
confidence: 75%
“…The so-called proton radius puzzle appears to be resolved. The puzzle emerged in 2010 when a muonic hydrogen measurement of the n = 2 Lamb shift [1] found that the very accurately measured proton charge radius R E = 0.8409(4) fm (or using a more conservative, model-independent analysis R E = 0.8413 (15) fm) disagreed with previous measurements of regular atomic hydrogen intervals [2], quoted in 2014 as R E = 0.8751(61) fm, as well as the state-of-the-art Mainz e − p scattering experiment (MAMI) [3,4] with a result of which links atomic units to SI [7,12], and settling on it and on the proton charge radius opens the possibility for further tests of quantum electrodynamics in atomic hydrogen. In its most recent update CODATA has adopted the small (muonic) radius value of 0.8414 (19) fm [13].…”
Section: Introductioncontrasting
confidence: 79%
“…[17] has a precision of 9 kHz, and the discrepancy between this measurement and the interval calculated [28] using the new, more accurate measurement of the proton charge radius from muonic hydrogen [19,20] is 13 kHz. The ongoing Lamb-shift measurement by our group has a precision goal of a few kHz, and, therefore, these shifts will have to be considered very carefully.…”
Section: The H(n=2) Lamb Shiftmentioning
confidence: 99%